Novel device-based therapies to improve outcome in ST-segment elevation myocardial infarction. Issue 6 (24th March 2021) - De Maria, Giovanni Luigi; Garcia-Garcia, Hector M; Scarsini, Roberto; Finn, Aloke; Sato, Yu; Virmani, Renu; Bhindi, Ravinay; Ciofani, Jonathan L; Nuche, Jorge; Ribeiro, Henrique B; Mathias, Wilson; Yerasi, Charan; et al.
Abstract: Primary percutaneous coronary intervention (PPCI) has dramatically changed the outcome of patients with ST-elevation myocardial infarction (STEMI). However, despite improvements in interventional technology, registry data show little recent change in the prognosis of patients who survive STEMI, with a significant incidence of cardiogenic shock, heart failure, and cardiac death. Despite a technically successful PPCI procedure, a variable proportion of patients experience suboptimal myocardial reperfusion. Large infarct size and coronary microvascular injury, as the consequence of ischaemia–reperfusion injury and distal embolization of atherothrombotic debris, account for suboptimal long-term prognosis of STEMI patients. In order to address this unmet therapeutic need, a broad-range of device-based treatments has been developed. These device-based therapies can be categorized according to the pathophysiological pathways they target: (i) techniques to prevent distal atherothrombotic embolization, (ii) techniques to prevent or mitigate ischaemia/reperfusion injury, and (iii) techniques to enhance coronary microvascular function/integrity. This review is an overview of these novel technologies with a focus on their pathophysiological background, procedural details, available evidence, and with a critical perspective about their potential future implementation in the clinical care of STEMI patients. Graphical Abstract: